Experimental Glucocorticoid Receptor Agonists for the Treatment of Asthma: A Systematic Review - Rogliani P; Ritondo BL; Puxeddu E; Pane G; Cazzola M; Calzetta L (Dove Medical Press, 2020)
Paola Rogliani,1,2 Beatrice Ludovica Ritondo,1 Ermanno Puxeddu,2 Gloria Pane,2 Mario Cazzola,1 Luigino Calzetta3 1Unit of Respiratory Medicine, Department of Experimental Medicine, University of Rome “Tor Vergata”, Rome, Italy; 2Division of Respiratory Medicine, University Hospital “Tor Vergata”, Rome, Italy; 3Department of Medicine and Surgery, Respiratory Disease and Lung Function Unit, University of Parma, Parma, ItalyCorrespondence: Paola RoglianiDepartment of Experimental Medicine, Via Montpellier 1, Rome 00133, ItalyTel +39 06 2090 4656Email paola.rogliani@uniroma2.itAbstract: Inhaled corticosteroids (ICSs) are considered the cornerstone of asthma treatment. Despite the solid evidence documenting the efficacy and safety of ICSs at the level of the airways, their use can be affected by pulmonary and systemic adverse events (AEs) when administered chronically and/or at high doses. Thus, there is a pharmacological and medical need for new glucocorticoid (GC) receptor (GR) ligands with a more favorable therapeutic index, in order to overcome the shortcomings of currently available ICSs. The therapeutic profile of GCs can be improved by enhancing genomic mechanisms mediated by transrepression, which is assumed to be responsible for several anti-inflammatory and immunomodulatory actions, rather than transactivation, which causes most of the GC-associated AEs. It was assumed that an independent modulation of the molecular mechanisms underlying transactivation and transrepression could translate into the dissociation of beneficial effects from AEs. Therefore, current research is looking for GCs that are able to elicit prevalently transrepression with negligible transactivating activity. These compounds are known as selective glucocorticoid receptor agonists (SEGRAs). In this review, experimental GR agonists currently in pre-clinical and clinical development for the treatment of asthma have been systematically assessed. Several compounds are currently under pre-clinical development, but only three novel experimental GR agonists (GW870086X, AZD5423, AZD7594) seem to have some potential therapeutic relevance and have entered clinical trials for the treatment of asthma. Since data from pre-clinical studies have not always been confirmed in clinical investigations, well-designed randomized controlled trials are needed in asthmatic patients to confirm the potentially positive benefit/risk ratio of each specific SEGRA and to optimize the development strategy of these agents in respiratory medicine.Keywords: asthma, glucocorticoid agonists, SEGRA, efficacy, safety